Full endoscopic resection of thoracic paravertebral schwannoma - Hongyu Song; Naikun Sun; Zhongguo Liu; Gang Rui; Baoshan Hu (Interdisciplinary Neurosurgery, 2023)
Objective: Thoracic paravertebral schwannoma is originated in Schwann cells that encompass the peripheral nerve fibers. Although conventional thoracotomy or thoracoscopic surgical strategy is identified as standard technique for the resection, we herein report a case of a thoracic paravertebral benign schwannoma successfully treated with full-endoscopic technique. Methods: A 47-year-old female was found a lesion in the right posterior mediastinum when she received a chest CT two weeks prior. The patient presented with no symptoms. She underwent posterior endoscopic resection of the lesion. To our knowledge, this is the first case of full endoscopic surgical treatment to deal with a thoracic paravertebral schwannoma pronounced to date. Results: Considering the dimension of the tumor and its surroundings, we performed gross-total resection through endoscopic approach. This technique was safe and effective in this patient. Conclusions: Full endoscopic resection is suitable for thoracic paravertebral schwannoma in certain populations.